HAMBATAN TERCAPAINYA SUSTAINABLE SUPPLY CHAIN MANAGEMENT (SSCM) INDUSTRI KELAPA SAWIT DI INDONESIA - Rangga Primadasa; Akh Sokhibi (JURNAL REKAYASA SISTEM INDUSTRI, 2018)
This study aims to identify barriers on sustainable supply chain management (SSCM) implementation for palm oil industries in Indonesia. Simple Additive Weighting (SAW) , one of Multi Criteria Decision Making (MCDM) method is chosen in this study because of the simplicicty and most suitable for palm oil industries case. The outputs of this study, there are 29 barriers on sustainable supply chain management (SSCM) for palm oil industries in Indonesia, all of its breakdown from their own key performance indicator (KPI) of SSCM. Three biggest barriers are (1) less management commitment (0.99); (2) bad relationship with society around the company (0.873); (3) Less efficient on FFB (Fresh Fruit Bunch) Process (0.873). While three least barriers are (1) No take-back policies on CPO Trading (0.718); (2) Less discipline from employee using earplug (0.718); (3) Less careful from employee while operate machinery (0.718).